2010
DOI: 10.1161/circulationaha.110.955302
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Systemic Myeloperoxidase Are Associated With Coronary Plaque Erosion in Patients With Acute Coronary Syndromes

Abstract: Background-Systemic levels of myeloperoxidase predict prognosis in patients with acute coronary syndromes and are considered a marker of plaque vulnerability. It is not known whether myeloperoxidase is associated with different coronary morphologies (ie, rupture or erosion of the culprit lesion) in patients with acute coronary syndrome. Methods and Results-Twenty-five consecutive patients (aged 67Ϯ11 years; 15 men [60%]; 13 [52%] with non-STsegment elevation acute coronary syndrome and 12 [48%] with acute ST-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
120
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(138 citation statements)
references
References 58 publications
8
120
0
2
Order By: Relevance
“…To the best of our knowledge, this is the first demonstration of such an event taking place in human patients. Activation of neutrophils across the coronary vascular bed is a hallmark of acute coronary syndromes (30,31,37). Activated neutrophils release the content of their primary granules in the blood: MPO circulating levels in particular are associated with and may predict clinical outcomes in patients with AMI (30,31,37,46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first demonstration of such an event taking place in human patients. Activation of neutrophils across the coronary vascular bed is a hallmark of acute coronary syndromes (30,31,37). Activated neutrophils release the content of their primary granules in the blood: MPO circulating levels in particular are associated with and may predict clinical outcomes in patients with AMI (30,31,37,46).…”
Section: Discussionmentioning
confidence: 99%
“…Platelets tightly interact with neutrophils and contribute to their activation and recruitment in inflamed tissues via multiple signals: P-selectin, together with b 2 and b 3 integrins, plays a key role (51,52). In turn, the activation of neutrophils, which is effective at fighting invading microbes, is deleterious in conditions of sterile vascular injuries, such as the thrombosis of coronary atherosclerotic plaques (37). The release of the PTX3 prestored in neutrophil granules during AMI may contribute to interrupt this loop, via modulation of events down- stream of P-selectin recognition, including b 2 integrin upregulation and heteroaggregate formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That study demonstrated that the fibrin content increased in association with the ischemic time, ranging from 48.4± 21% (<3 hours) up to 66.9±9% (>6 hours) (p = 0.02), whereas the platelet content decreased from 83) . That study consisted of two substudies including 25 ACS patients and 22 sudden coronary death victims.…”
Section: Coronary Thrombus Components and The Ischemic Timementioning
confidence: 85%
“…Of interest, the change in fibrous cap thickness had a significant positive correlation with changes in CRP levels (r=0.44, p<0.01). A recently published study by Ferrante et al (Ferrante et al, 2010) enrolled 25 consecutive ACS patients undergoing percutaneous coronary intervention and OCT assessment, evaluating the relationship between plaque morphology and serum levels of myeloperoxidase (MPO) and CRP. OCT classified the culprit lesion as ruptured in 18 (72%) or eroded in 7 patients (28%) and detected intraluminal thrombus in 89% of ruptured plaques and 100% of eroded plaques.…”
Section: Soluble Biomarkersmentioning
confidence: 99%